SPECIES OF FILENCHUS ANDRASSY, 1954 FROM MANIPUR WITH DESCRIPTION OF FILENCHUS NEOLONGICAUDATUS SP. NOV. - L. BINA; N. MOHILAL (The Bioscan, 2010)
During a survey carried out in the valley districts of Manipur in order to find out the plant parasitic nematodes associated with mulberry plants, Morus spp. and pine trees, three species of Filenchus Andrassy, 1954 were discovered. Among them, one is recorded as a species new to science. Filenchus neolongicaudatus sp. nov. is characterized by having a long body of 0.49-0.71mm, a long tail of 144.5-248.2μm length and spear of 17- 18.7μm length. The genus Filenchus is reported for the first time from Manipur.